Assessment of the Thermal Power of Groundwater Intakes in The Kielce District - Nartowska, Edyta; Budzianowski, Dominik; Styś-Maniara, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of the article was to estimate the thermal power of groundwater intakes of the Kielce district within the sheets of hydrogeological maps with the serial numbers MHP 813-817, MHP 850-851, and to indicate in this area prospective areas for the development of low-temperature geothermal energy supported by water/water heat pumps.
Keywords: low-temperature geothermal; RES; thermal power; energy efficiency index; groundwater intake; heat pumps; geotermia niskotemperaturowa; OZE; moc cieplna; wskaźnik efektywności energetycznej; ujęcie wód podziemnych; pompa ciepła